채소 종자별 온탕침지 종자소독 효과검정 - 이지현(Ji-Hyun Lee); 신순선(Shun-Shan Shen); 박용주(Yong-Ju Park); 류경열(Kyung-Yul Ryu); 지형진(Hyeong-Jin Jee) (Sigmulbyeong yeon'gu, 2007)
Hot water treatment that is the most appropriate seed disinfection method for organic vegetable farming was evaluated in this study. Among the leafy vegetable seeds lettuce that was the most sensitive to hot water was suitable to treat at $45^{°}C$ for 25 min, while Chinese cabbage and radish seeds were optimally treated at $50^{°}C$ for 25 min. The treatments resulted in similar or higher seed germination rate than non-treated seeds and promoted plant growth. In addition, fungi such as Alternaria, Aspergillus, Penicillium, or Mucor grown on the seeds were suppressed over 90% and the bacterial growth on lettuce seeds reduced 98.5% by the treatment. Among the fruit vegetable seeds pumpkin that was vulnerable to hot water was suitable to treat at $50^{°}C$ for 15 min, while cucumber and hot pepper seeds revealed optimum treatment at $50^{°}C$ for 25 min as chinese cabbage and radish. The treatment also showed similar or higher seed germination rate and growth than non-treated seeds. Furthermore, fungi such as Rhizopus, Aspergillus, Penicillium or Mucor grown on the seeds reduced from 72.0% to 95.4%. The bacterial growth on cucumber and red pepper seeds was suppressed from 65.5% to 86.0% by the treatment. Results indicated that the hot water treatment is practical for disinfection of organic vegetable seeds and the optimum temperature and soaking time varied among the seeds. 본 연구는 유기농 채소종자의 소독방법으로 가장 적합한 온탕침지법을 개발하고자 수행하였다. 엽채류 중 열에 비교적 민감한 상추 종자의 최적 온탕침지 조건은 $45^{°}C$ 25분이었으며 배추와 무 종자 $50^{°}C$ 25분이었다. 온탕침지로 이들 종자의 발아율과 생장은 무처리와 비슷하거나 촉진되었고, Alternaria, Aspergillus, Penicillium, Mucor 등의 종자감염 곰팡이는 90% 이상 혹은 100% 억제되었으며 상추 종자에 감염된 세균 억제효과는 98.5%였다 오이, 고추, 호박 등 과채류 종자 중에는 호박이 가장 온수에 감수성이었는데 $50^{°}C$ 15분 침지가 적합하였고 오이와 고추 종자는 $50^{°}C$ 25분 처리가 가장 효과적이었다. 온탕 침지한 오이 및 호박 종자의 발아율 및 생장은 무처리와 비슷하거나 약간 높았는데, 고추의 경우에는 발아율은 50% 이상 증가되었으며 뿌리생장은 5배 이상 신장되었다. 이들 종자에 감염된 곰팡이 중 Rhizopus, Aspergillus, Penicillium, Mucor등의 억제율은 $72%{\sim}95.4%$였고 감염세균의 억제율은 $65.5%{\sim}86.0%$였다. 본 시험의 결과로 볼 때 온탕침지의 최적 조건은 종자에 따라 다소 다르며, 온탕침지는 모든 종자전염성 병원균을 방제할 수는 없으나 이들을 효과적으로 억제할 수 있는 기술로 유기농업에서 유용하게 활용할 수 있을 것으로 기대된다.